HAND-ON ACTIVITIES IN ENGLISH LEARNING GROUND LEVEL AT SOS CHILDREN’S VILLAGE BALI - Dewi, Ni Putu Ayu Kartika Sari; Septiana, Kadek Ayu Kartika; Pratama, Ngurah Artha Yoga; Suamba, I Made; Wulantari, Ni Putu; Wiastra, I Gede Gita; Mawa, I Wayan; Wiwintari, Ni Luh Gede (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Hands on is a learning design aimed at involving students in finding information, asking questions, engaging in activities, discovering, and concluding. Known as authentic learning or experiential education, hands on creates an active learning environment. The aims to describe the emergence and benefits of hands on conducted at SOS Children’s,Bantas, this qualitative study with a descriptive method seeks to illustrate how hands on can facilitate students in gaining knowledge from direct learning experiences and to clarify the benefits of hands on activities. Data was collected through observation and interviews. Findings show that hands on appeared in student activities, including actively asking questions, engaging directly with objects during learning, and developing critical thinking, independence, and activeness in students.